Geopolítica petrolera y autoritarismo en América Latina y el Caribe: el caso Venezuela - Arnoldo Pirela (Caravelle)
This paper focuses on the armed conflicts in Central America in the late 70s and 80s, as they relate to the so-called “turn to the left”, which began with Hugo Chávez in 1999. It suggests a reading based on the economic and political history of Venezuela, taking into consideration its development strategy of using oil revenues to break tax dependency from oil. It is in fact the story of a mainly pragmatic nationalism with a social democratic orientation that completes a virtuous circle by the oil industry nationalization in 1976, only to find itself trapped in the limitations of its conflicting strategy; and, with the turn of the century, leading the country into the hands of a successful convergence operation between the traditional authoritarianism of military lodges and the totalitarianism of Soviet-cuban inspiration.